Preferential crediting as a tool for stimulating the development of the tourism industry - Khursanova F.E. (THE INNOVATION ECONOMY, 2026)
The article examines the role of preferential lending as a strategic tool for supporting and developing the tourism industry. The features of providing preferential loans, their impact on the financial stability of small and medium-sized tourism enterprises, infrastructure modernization, and the introduction of innovative services are analyzed. Special attention is paid to the practical aspects of implementing preferential lending programs, including reducing interest rates, state guarantees, and supporting investment activity. The conclusion was made that concessional loans